Consumers Food Delivery Apps (FDAs) Continuance Intention: An Empirical Investigation using the Extended UTAUT2 Model (Global Journal of Management and Business Research, 2023)
Online food delivery applications FDAs a novel alternative marketing channel have been extensively adopted by both enterprises and customers in the restaurant sector Despite the changing consumer attitude towards FDA services there is still a dearth of research on understanding consumers continued intention to use FDA services in Bangladesh s expanding food delivery market particularly after the COVID-19 pandemic To attain this goal this study employed the widely used Extended Unified Theory of Acceptance and Use of Technology UTAUT2 The model was tested was evaluated using partial least square structural equation modeling PLS-SEM on 350 respondents According to the findings of the study performance expectancy social influence facilitating conditions hedonic motivation price value information quality and convenience are all critical factors in maintaining the desire to utilize FDA services in Bangladesh However effort expectancy habit and time-saving were insignificant in the context of Bangladesh This study contributes theoretically and practically to academics and practitioners working in areas related to online FDAs services
Keywords: UTAUT2; food delivery apps; FDAs; continuance usage intention; online shopping; bangladesh; online food delivery service